Extrapolating Metabolic Savings in Running: Implications for Performance Predictions - Kipp, Shalaya; Kram, Rodger; Hoogkamer, Wouter (Frontiers in Physiology, 2019)
Training, footwear, nutrition, and racing strategies (i.e. drafting) have all been shown to reduce the metabolic cost of distance running (i.e. improve running economy). However, how these improvements in running economy quantitatively translate into faster running performance is less established. Here, we quantify how metabolic savings translate into faster running performance, considering both the inherent rate of oxygen uptake-velocity relation and the additional cost of overcoming air resistance when running overground. We collate and compare five existing equations for oxygen uptake-velocity relations across wide velocity ranges. Because the oxygen uptake vs. velocity relation is non-linear, for velocities slower than 3 m/s, the predicted percent improvement in velocity is slightly greater than the percent improvement in running economy. For velocities faster than 3 m/s, the predicted percent improvement in velocity is less than the percent improvements in running economy. At 5.5 m/s, i.e. world-class marathon pace, the predicted percent improvement in velocity is 2/3rds of the percent improvement in running economy. For example, at 2:04 marathon pace, a 3% improvement in running economy translates to a 1.97% faster velocity or 2:01:36, almost exactly equal to the recently set world record.